The Journey of the Villain: A Character Analysis of the Once-Ler from Dr. Seuss’ The Lorax - Muhammad Sultan Pasya; Isti Siti Saleha Gandana; Nia Nafisah (Universitas Pendidikan Indonesia (UPI), 2020)
Heroism has become a much-discussed topic in literary studies. However, the villain, who shares the same important role as the hero, does not generally receive as much recognition within these studies. For this reason, this research was conducted to analyze the villain of the story to contribute more into the discussion. The character that was analyzed is the Once-ler from The Lorax (1971) by Dr. Seuss. The Once-ler is the main antagonist of The Lorax (1971) that possesses interesting journey to look into. He goes through a journey that changes his characterization in a certain point of his journey. The Hero’s Journey theory (Vogler, 1992/1999) and Character Arc theory (Weiland, 2016), thus, were adopted to analyze both the journey and the changes in character that the Once-ler experiences. The result shows that the Once-ler’s journey is a Shadow’s journey, and that he experienced both Positive and Negative Change Arc that made him a Redeemed Villain, which is different from most of the villains. This research also discussed the similarities between the hero and the villain that leads to a conclusion that heroes and villains can be differentiated by how they finish their journey; if they succeed, they are the heroes, and if they failed, they are the villains.Keywords: Character Arc, Hero’s Journey, The Lorax, The Once-ler, Villain’s Journey